2020
DOI: 10.3390/f11060607
|View full text |Cite
|
Sign up to set email alerts
|

Role of Root and Stem Base Fungi in Fraxinus angustifolia (Vahl) Dieback in Croatian Floodplain Forests

Abstract: Large-scale ash (Fraxinus spp.) dieback caused by the fungus Hymenoscyphus fraxineus has been a major concern throughout Europe for more than two decades. Most of the related research has been focused on Fraxinus excelsior L., and there is still little information on fungal involvement in the dieback of Fraxinus angustifolia Vahl, especially in roots and stem bases, which play an important role in decline progress and tree stability. The objectives of this study were to identify fungi present in visually healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…To our knowledge, this is the first report of N. punicea on common ash trees in B&H. N. punicea has a wide host range, and it was previously reported in multiple hosts in Europe, Asia, and North America ( Booth, 1959 ; Hirooka et al, 2013 ; Langer, 2017 ). This fungus has also been reported in common ash in Germany ( Langer, 2017 ; Meyn et al, 2019 ) and recently in the narrow-leaved ash in neighboring Croatia ( Kranjec Orlović et al, 2020 ). In B&H, N. punicea ( Nectria punicea var.…”
Section: Discussionsupporting
confidence: 67%
“…To our knowledge, this is the first report of N. punicea on common ash trees in B&H. N. punicea has a wide host range, and it was previously reported in multiple hosts in Europe, Asia, and North America ( Booth, 1959 ; Hirooka et al, 2013 ; Langer, 2017 ). This fungus has also been reported in common ash in Germany ( Langer, 2017 ; Meyn et al, 2019 ) and recently in the narrow-leaved ash in neighboring Croatia ( Kranjec Orlović et al, 2020 ). In B&H, N. punicea ( Nectria punicea var.…”
Section: Discussionsupporting
confidence: 67%
“…Other studies have shown a frequent association of declining ash trees with secondary root pathogens such as Armillaria spp. (Lygis et al, 2005;Skovsgaard et al, 2010;Langer, 2017;Kranjec Orlović et al, 2020;Peters et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have revealed that ash decline is more probably driven by a complex of multiple interacting factors, including other fungal species, which contribute to and accelerate this process [5,6]. Ash trees are asymptomatically colonized by a variety of endophytic fungi, which can become opportunistic pathogens and spread in weakened tissue, especially when the host undergoes vitality loss caused by biotic or abiotic stresses [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%